The changing face of retirement: Future patterns of work, health, care and income among the older population - Carl Emmerson; Katherine Heald; Andrew Hood (Institute for Fiscal Studies (IFS), 2014)
This report presents projections of mortality, family composition, health, care receipt, care provision, labour supply and receipt of disability benefits for people aged 65 and over from 2010-11 through to 2022-23, as well as projections of their wealth and incomes, in order to offer commentary on the net income distribution and rates of poverty for those aged 65 and over through to the early 2020s. We also discuss the effect some alternative policy scenarios could have on the evolution of these incomes.
Keywords: 330